2000
DOI: 10.1038/sj.ijir.3900521
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic stimulation of the cavernous nerve for the treatment of erectile dysfunction in humans

Abstract: A recent study in dogs has demonstrated that magnetic stimulation (MS) of the cavernous nerve produced an increase of the intracorporeal pressure and full penile erection. In view of these results, we tested the possible application of this procedure in humans with erectile dysfunction (ED). The study comprised 32 patients with ED (age 38.3 AE 9.6 y) and 20 healthy volunteers (age 36.8 AE 8.8 y). Routine erectile function tests suggested that impotence was neurogenic. A magnetic coil was placed over the dorsal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Through evolution, the human penis has lost structures such as the penis bone. Thus, the penis needs to expand several times in size during sexual intercourse, and the bulbocavernosus reflex during erection rigidity causes the intracorporal pressure to exceed the systolic blood pressure 1 , 2 . During this process, erectile signals are transmitted to the corpora cavernosa (CC) by activation of the parasympathetic nervous system and signal transfer in the sacral erectile centre, regulating the nitric oxide synthase (NOS)/cGMP cascade, subsequently leading to depolarisation followed by smooth muscle relaxation with consecutively increased blood inflow 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Through evolution, the human penis has lost structures such as the penis bone. Thus, the penis needs to expand several times in size during sexual intercourse, and the bulbocavernosus reflex during erection rigidity causes the intracorporal pressure to exceed the systolic blood pressure 1 , 2 . During this process, erectile signals are transmitted to the corpora cavernosa (CC) by activation of the parasympathetic nervous system and signal transfer in the sacral erectile centre, regulating the nitric oxide synthase (NOS)/cGMP cascade, subsequently leading to depolarisation followed by smooth muscle relaxation with consecutively increased blood inflow 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…A pioneer study investigated impulse magnetic-field therapy on patients with neurogenic ED and healthy volunteers. The study concluded that magnetic stimulation is a simple, noninvasive method that could induce penile engorgement and indicated this therapy might be suitable for patients with ED [64] . Another double-blind, placebo-controlled study assessed the efficacy of 3 weeks of impulse magnetic-field therapy for ED and found that impulse magnetic-field therapy improved erectile function [65] .…”
Section: Resultsmentioning
confidence: 96%
“…So far, rTMS has been used for repairing of damaged peripheral nerves [3]. Some reported therapeutic effect on neurogenic bladder [4], and magnetic stimulation of the cavernous nerve was reported can induce penile erection [5]. However, there is no report of rTMS treating for NSD.…”
Section: Discussionmentioning
confidence: 99%